Knowledge, Power, and the Struggle to Write: Social Barriers in Research Proposal Development among English Literature Students - Karnedi, Karnedi; Asril, Lelly Zuyana; Estuhono, Estuhono (Baileo: Jurnal Sosial Humaniora, 2025)
This study investigates the social and linguistic barriers encountered by English literature students in developing research proposals, focusing on the interplay between knowledge, power, and academic writing. It aims to identify key difficulties faced by students and evaluate the impact of the Linguistics Research Methods (LRM) course in addressing these challenges. Employing a mixed-methods approach, the study involved 32 undergraduate students from Universitas Persada Bunda Indonesia and utilized both questionnaires and tests, including pre- and post-assessments of proposal writing. The evaluation covered five core indicators: organization, logical development of ideas, grammar, punctuation and mechanics, and style and expression. The findings show a notable improvement in students’ writing performance after completing the LRM course. The average pre-test score was 54, while the post-test score rose to 72, indicating a significant enhancement in their proposal-writing skills. Nevertheless, students struggled with key aspects such as articulating research focus, distinguishing literature reviews from problem statements, and presenting their ideas in clear, academic language. These challenges point to deeper issues of epistemic access and uneven academic capital. This research contributes novel insight into how academic gatekeeping and unequal access to research literacy intersect within undergraduate education. It recommends a pedagogical emphasis on critical academic writing, reflective inquiry, and inclusive mentorship to support students’ entry into scholarly communities. These findings have broader implications for improving higher education practices in the social sciences and humanities, particularly in non-native English contexts.